Phenylboronic ester-modified anionic micelles for ROS-stimuli response in HeLa cell - Qi Y. Wang; Yi S. Xu; Nan X. Zhang; Zhi P. Dong; Bo N. Zhao; Lin C. Liu; Tao Lu; Yue Wang (Taylor & Francis Group, 2020)
Smart polymers as ideal drug nanocarriers have attracted much attention due to the effective drug delivery, internalization and release once triggered by intracellular stimuli, as well as reduced cytotoxicity. We here reported the anionic micelle consisting of copolymer (PEG-b-PAsp) and a PBE (Phenylboronic Ester) group grafted, which can achieve fast response to intracellular ROS and enhanced anti-tumor activity. With this, PEG-b-PAsp-g-PBE/DOX system showed better tumor growth inhibition when studied on HeLa cell lines with high level of intracellular ROS and its subcutaneous tumor models. Additionally, the administration of PEG-b-PAsp-g-PBE/DOX did cause significantly lower systemic toxicity in comparison with free DOX. Hence, PEG-b-PAsp-g-PBE could be a highly efficient and safe nanocarrier to improve the efficacy of chemotherapeutic.